Analysis of Flavonoid and Tannin Contents in Pumpkin Seed (Cucurbita moschata) Extract - Adi Fahri; Sutrisnawati Sutrisnawati; Manap Trianto; Zulaikhah Dwi Jayanti; Fatmah Dhafir; Masrianih Masrianih (Biology, Medicine, & Natural Product Chemistry, 2026)
Pumpkin is one of the herbal plants that possesses various medicinal properties, including antidiabetic, antifungal, antibacterial, anti-inflammatory, and antioxidant activities, due to the presence of bioactive compounds in its seeds. This study aimed to identify the bioactive compounds present in pumpkin seed extract using qualitative and quantitative descriptive methods. Qualitative analysis was conducted through color reaction tests using several specific reagents to identify the presence of flavonoid and tannin compounds. Quantitative analysis was performed using the UV-Vis spectrophotometric method based on standard solution calibration curves to determine the concentration of each compound. The qualitative test results indicated that the pumpkin seed extract positively contained flavonoids and tannins, as evidenced by the formation of specific color changes in each test. The quantitative analysis showed that the average flavonoid content was 9.34 mg/g, while the average tannin content was 9.42 mg/g. Based on the results of this study, it can be concluded that pumpkin seed extract contains high levels of flavonoid and tannin compounds, indicating its potential as a natural source of antioxidants. This study is expected to serve as a basis for further development regarding the potential utilization of pumpkin seeds with pharmacological effects.